Dry Eye Disease: Early Recognition with Guidance on Management and Treatment for Primary Care Family Physicians - Verjee, Mohamud A. (Ophthalmol Ther, 2020)
Primary care presentations of dry eye disease (DED) are common and pose a diagnostic challenge due to the variety of symptoms and the absence of certainty for family practitioners. While there are many published articles on the topic, the 2017 Tear Film and Ocular Surface Society Dry Eye Workshop was a landmark report in distinguishing multifactorial differences. Redefined terms clarified the DED disorder. The ocular surface—the tear/air interface—is the primary refractive component of the eye, which is why DED is so significant and impacts vision. There is a high prevalence of DED in the community, ranging from 5% to 30% of people across multiple studies. Elderly patients have up to 75% increased risk of DED and receive more intensive treatment than younger age groups. DED is also more common in women than men, occurring in 9.8% of postmenopausal women. The causes of DED span defective lacrimal apparatus and systemic disorders. Despite its prevalence, up to one-half of patients with confirmed DED do not receive proper alleviating treatment. Risk factors on functional and environmental bases follow. Tools to elicit a diagnosis more confidently are outlined using the Ocular Surface Disease Index (OSDI) and the Symptom Assessment in Dry Eye questionnaires (SANDE). Lacritin, lutein, vitamin A, and balanced nutrition are essential contributors to maintaining healthy eyes with appropriate management and treatment. The authors hope that this paper will prompt a more accurate and expedient diagnosis of DED in primary care practice and an earlier recognition of specialist referrals. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s40123-020-00308-z) contains supplementary material, which is available to authorized users.